Integrity Character Education in Indonesia: Systematic Literature Review and Bibliometric Analysis - Umar Umar; Mahdi Hamzah; Rahmatullah Rahmatullah; Siar Ni'mah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Character education has been a national priority in Indonesia since 2017, with a focus on fostering integrity. Despite its significance, integrity development in character education remains underexplored in research and pedagogy, especially concerning millennial students and educators. This study used a Systematic Literature Review (SLR) with Bibliometric analysis following the PRISMA model. A total of 42 articles published between 2017 and 2023 were analyzed to identify research trends, methodologies, and findings in character education within Indonesian schools. The findings reveal that character education research has diversified into topics such as education, learning strategies, psychology, and social empiricism. However, notable gaps exist in addressing integrity-related themes, including state and national integrity, piety, and millennial challenges. Methodologically, most studies employed qualitative or quantitative approaches, with limited use of mixed methods, highlighting an area for methodological innovation in future research. The identified trends and gaps underscore the importance of addressing integrity as a central theme in character education. Mixed-method approaches could offer nuanced insights into this complex issue. Additionally, research emphasizing millennial educators and the interplay of piety and national identity would provide valuable contributions. This study offers a comprehensive overview of character education research in Indonesia, emphasizing the need for future studies to adopt mixed-method approaches and focus on integrity development. These findings have important implications for educational policy and pedagogy, shaping efforts to strengthen national character through education.